Penny Postcard of the first Foothills Hotel in Ojai, CA - United States Post Office::::::
The first Foothills Hotel was constructed in 1903 and designed by Samuel M. Ilsley. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.